Low-velocity penetrating trauma with anterior mitral leaflet perforation and left ventricular injury: Immediate and postoperative management - Sarah Kim; Jonathan Jou; Thomas Cartolano; Gregory Macaluso; Jane Kayle Lee (Trauma Case Reports, 2025)
Penetrating cardiac injury is a highly lethal injury often resulting in ventricular injury. We present a case of a low-velocity penetrating cardiac injury with pericardial tamponade from a left ventricle myocardial defect managed operatively with a pericardial window that was converted to a median sternotomy with stapled control of the left ventricular injury. Patient was subsequently diagnosed with mitral valve anterior leaflet perforation with left thrombus managed medically with anticoagulation. Our treatment highlights several considerations during operative management of traumatic cardiac injury.